Why antidiabetic drugs are potentially neuroprotective during the Sars-CoV-2 pandemic: The focus on astroglial UPR and calcium-binding proteins - Gonçalves, Carlos-Alberto; Sesterheim, Patrícia; Wartchow, Krista M.; Bobermin, Larissa Daniele; Leipnitz, Guilhian; Quincozes-Santos, André (Frontiers in Cellular Neuroscience, 2022)
We are living in a terrifying pandemic caused by Sars-CoV-2, in which patients with diabetes mellitus have, from the beginning, been identified as having a high risk of hospitalization and mortality. This viral disease is not limited to the respiratory system, but also affects, among other organs, the central nervous system. Furthermore, we already know that individuals with diabetes mellitus exhibit signs of astrocyte dysfunction and are more likely to develop cognitive deficits and even dementia. It is now being realized that COVID-19 incurs long-term effects and that those infected can develop several neurological and psychiatric manifestations. As this virus seriously compromises cell metabolism by triggering several mechanisms leading to the unfolded protein response (UPR), which involves endoplasmic reticulum Ca2+ depletion, we review here the bases involved in this response that are intimately associated with the development of neurodegenerative diseases. The discussion aims to highlight two aspects - the role of calcium-binding proteins and the role of astrocytes, glial cells that integrate energy metabolism with neurotransmission and with neuroinflammation. Among the proteins discussed are calpain, calcineurin and sorcin. These proteins are emphasized as markers of the UPR and are potential therapeutic targets. Finally, we discuss the role of drugs widely prescribed to patients with diabetes mellitus, such as statins, metformin, and calcium channel blockers. The review assesses potential neuroprotection mechanisms, focusing on the UPR and the restoration of reticular Ca2+ homeostasis, based on both clinical and experimental data.